2007
DOI: 10.1007/s10551-006-9281-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Design Science of Ethical Decision Support

Abstract: Cognition, decision support systems, design science, emotion, ethics, group support systems, philosophy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 105 publications
0
21
0
Order By: Relevance
“…Indeed Mathieson (2007) suggested that ethical decisions commonly involve uncertainty and confliction and therefore are some of the most complex and difficult decisions that individuals make.…”
mentioning
confidence: 99%
“…Indeed Mathieson (2007) suggested that ethical decisions commonly involve uncertainty and confliction and therefore are some of the most complex and difficult decisions that individuals make.…”
mentioning
confidence: 99%
“…Individuals ranging from military commanders to manufacturing floor managers to trial juries may be subject to cognitive distortions that include availability, representativeness, anchoring and adjustment, and confirmation biases [17,28,33,37]. Humans’ probabilistic reasoning ability is poor, and both physicians and patients may inaccurately interpret single probabilities, conditional probabilities, and relative risks when making decisions [52].…”
Section: Resultsmentioning
confidence: 99%
“…However, IS academics (Ackoff, 1989;Fricke, 2009;Intezari & Pauleen, 2014;Jennex, 2009) have questioned this formulation of the knowledge hierarchy. For example, in a paper on ethical decision support, Mathieson (2007) states that accumulating wisdom may be the most important outcome of ethical decision-making, one that can be fed back into ethical DSSs to make the results available to others. It is important to reiterate that while knowledge may be necessary for wisdom, it is not sufficient.…”
Section: (A Abstractearch In Googlementioning
confidence: 99%
“…Even outside of IS journals, we find explicit mention of wisdom in relation to IS with regard to ethics. For example, in a paper on ethical decision support, Mathieson (2007) states that accumulating wisdom may be the most important outcome of ethical decision-making, one that can be fed back into ethical DSSs to make the results available to others. However, ethics and values are better seen as facets of wisdom, not wisdom itself.…”
Section: (A Abstractearch In Googlementioning
confidence: 99%